Revisão sistemática de estudos da divergência genética e sua associação com vigor híbrido em aveia branca - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The white oat (Avena sativa L.) has great importance as an alternative winter crop with a wide area of cultivation in Brazil, especially in the southern region of the country. The evaluation of genetic dissimilarity is an important tool to assist cultivars selection, since it allows greater convenience in identifying genotypes with desired characteristics, meeting the need for dynamic, fast and economically efficient breeding. Thus, this research aims to analyze existing data in the scientific literature about the effect of genetic dissimilarity on heterosis in white oats. For this purpose, a systematic review of the literature was performed from the selection and careful reading of articles, theses and dissertations found in the databases, selecting only the literature that met the inclusion criteria defined in this study. Only the publications that answered the study question, published from 1992 to 2020, in Portuguese and English, all types of methodological designs were accepted. The results obtained from this literature search demonstrate that the knowledge of the level of genetic dissimilarity between the parents is fundamental in the exploration of heterosis. However, this should not be the only factor to be considered. The combinatorial ability of the parents is what will define the greatest heterotic gain. Studies involving several analyses simultaneously, such as morphological, biochemical and molecular analyses, are of great importance, as they allow genetic dissimilarity to be evaluated in a more efficient way, minimizing evaluation errors. Among the molecular markers, the SSRs have presented themselves as a tool of great utility in determining the genetic divergence between cultivars of white oat, with the great advantage of not suffering environmental influence. Thus, we conclude that the analysis of genetic dissimilarity is of fundamental importance in the choice of genitors in order to explore the hybrid vigor in white oat.
Systematic review of studies of genetic divergence and its association with hybrid vigor in white oat
Keywords: Distância genética; Heterose; Avena sativa L; Genetic distance; Heterosis; CNPQ::CIENCIAS AGRARIAS